Impact of neoadjuvant immunotherapy combined with chemotherapy or chemoradiotherapy on postoperative safety in locally advanced esophageal squamous cell carcinoma: a propensity score-matched retrospective cohort study - Li, Yixin; Xiao, Gang; Yang, Bo; Hong, Yidan; Chen, Zeng; Gu, Lingling; Kong, Cheng; Zhao, Lijun; Zhu, Zihao; Xu, Qicen; Chen, Yu; Jiang, Ming; et al. (Frontiers in Oncology, 2025)
IntroductionThe combination of immunotherapy with neoadjuvant chemotherapy (nICT) or chemoradiotherapy (nICRT) represents a novel treatment approach for patients with locally advanced esophageal squamous cell carcinoma (LA-ESCC). This study aimed to compare postoperative complications between patients who underwent esophagectomy directly and those who received surgery following neoadjuvant immunotherapy combining treatments (nIComT) including nICT or nICRT.Materials and methodsA retrospective analysis was conducted on patients with LA-ESCC at our center. A 1:1 propensity score matching (PSM) was used to eliminate baseline characteristics differences. The primary endpoint was postoperative complications, which were assessed based on the Esophageal Cancer Complications Consensus Group (ECCG) criteria, and the severity was evaluated according to the Clavien-Dindo classification.ResultsAfter PSM, 116 matched patients were analyzed in both the surgery-alone and nIComT group. The overall complication rates between the two groups were similar (51.7% vs 56.0%, P=0.510). Incidence of cardiovascular complications, most of which were grade I and II, was increased in the nIComT group compared with the surgery-alone group(P=0.003). The higher rate of cardiovascular complications mainly due to hypotension (52.6% vs 42.2%, P=0.004) requiring intervention including the use of vasopressors, or transfusion. Additionally, more patients in the nIComT group received perioperative transfusion (34.5% vs 14.7%, P<0.001), as well as an extended operation duration (276 ± 66min vs 246 ± 63min, P<0.001), when compared to the surgery-alone group. The logistic regression analyses of potential risk factors for cardiovascular complications showed that receiving neoadjuvant treatment was independently associated with cardiovascular complications (OR=2.03, 95% CI=1.15-3.57, P=0.015).ConclusionOur study highlights an increased risk of cardiovascular complications among patients received nIComT, underscoring the significance of postoperative circulatory interventions. Further prospective studies are needed for validation.